Evaluation of different components of organic-mineral mixtures to be used on city lawns - V D Nagornyy; М М Fatijev (RUDN Journal of Agronomy and Animal Industries, 2012)
Feasibility of production of organic-mineral mixtures using composted manure, sapropel, dolomite, mineral fertilizers, hydrogel and formaldehyde has been shown. Such mixtures may have higher content of NPKCaMg and higher CEC and water holding capacity, and may be safely used on city lawns.